Answer:
[tex]\frac{3s^2-4}{s(s^2-4)}[/tex]
Step-by-step explanation:
Here, the question is to find the Laplace transformation of [tex]f(t)[/tex]
where, [tex]f(t)=(e^t-e^{-t})^2[/tex]
We know that for [tex]t>0[/tex], [tex]\mathcal{L}\{f(t)\} =\int_0^{\infty} e^{-st}f(t)dt[/tex]
[tex]\mathcal{L}\{e^{at}\}=\int_0^{\infty} e^{-st}e^{at}dt[/tex]
[tex]\Rightarrow \mathcal{L}\{e^{at}\}=\int_0^{\infty} e^{(a-s)t}dt[/tex]
[tex]\Rightarrow \mathcal{L}\{e^{at}\}=\left[\frac { e^{(a-s)}}{a-s}\right]_0^{\infty}[/tex]
[tex]\Rightarrow \mathcal{L}\{e^{at}\}=\frac { 1}{s-a}\cdots(i)[/tex]
Here, we have [tex]f(t)=(e^t-e^{-t})^2[/tex]
[tex]\Rightarrow f(t)=(e^t)^2+(e^{-t})^2-2(e^t)(e^{-t})[/tex]
[tex]\Rightarrow f(t)=e^{2t}+e^{-2t}-2e^{0t}[/tex]
So, the laplace transformation of [tex]f(t)[/tex] is
[tex]\mathcal{L}\{f(t)\}=\mathcal{L}\{e^{2t}+e^{-2t}-2e^{0t}\}[/tex]
[tex]\Rightarrow \mathcal{L}\{f(t)\}=\mathcal{L}\{e^{2t}\}+\mathcal{L}\{e^{-2t}\}+\mathcal{L}\{e^{0}\}[/tex]
Now, using equation[tex](i)[/tex]
[tex]\mathcal{L}\{f(t)\}=\frac{1}{s-2}+\frac{1}{s-(-2)}+\frac{1}{s-0}[/tex]
[tex]\Rightarrow \mathcal{L}\{f(t)\}=\frac{1}{s-2}+\frac{1}{s+2}+\frac{1}{s}[/tex]
[tex]\Rightarrow \mathcal{L}\{f(t)\}=\frac{3s^2-4}{s(s^2-4)}[/tex]
Hence, the Lapelace transformation of [tex]f(t)=(e^t-e^{-t})^2[/tex] is
[tex]\frac{3s^2-4}{s(s^2-4)}[/tex].